Mothers’ Knowledge toward Home Care for Children with Wilms Tumors at Pediatric Hospitals in Bagdad City - Rehab A. Ali; Zaid W. Ajil (Indian Journal of Forensic Medicine & Toxicology, 2021)
Objectives: To find out relationships between mothers’ knowledge and their demographic characteristics thatincludes (age, marital status, level of education, family income, home location, number of family members.Methods: A descriptive research was performed from October 1, 2020, to June 1, 2021, Non - probability(purposive) sample. In which the sample was objectively chosen from (100) mothers who participated in thestudy and were obtained from three Baghdad hospitals. It included 47 mothers at the Child welfare TeachingHospital and 28 at the Central Child Teaching Hospital and 25 in the city of Miamian al-Kadhimin (peacebe upon them both) in Baghdad.Results: Mothers’ knowledge towards homecare for “Children with Wilms Tumours” at pediatric hospital’sitems was not assigned at the established level in which that achieving the goal of this study.Conclusion: Mothers’ knowledge towards homecare for “Children with Wilms Tumours” at pediatrichospital’s items was not assigned at the established level in which that achieving the goal of this study.